Analysis and Design of Purchasing and Sales Information Systems Using the Prototype Method - Zahara; Gusti Alex Candra, Dori; Al Ashari, Muhammad; Permana Putra, Budi (Expert Net: Exploration Journal of Technological Education Trends, 2025)
Advances in communication and information technology have transformed various sectors, including the retail sector. Toko Pustaka Muslim in Bengkalis Regency, which sells Muslim products, previously relied on manual processes for recording transactions and managing inventory. This led to inefficiency, errors in transaction recording, and delays in decision making. To overcome this problem, this study designed a web-based information system that automates the process of recording sales and purchase transactions and managing inventory in real-time. The system was designed using the prototyping method with an iterative approach that involved direct evaluation from users, as well as utilizing Unified Modeling Language (UML) for design visualization and Figma for the user interface. The results of the study show that the system built was successfully implemented and was able to improve the operational efficiency of the store. Based on the tests conducted, the system was proven to minimize inventory recording errors and was able to present accurate report data, thereby accelerating the decision-making process by store owners compared to the previous manual system.